Plasma Transferrin Concentration as a Nutritional Marker in Malnourished Dogs with Nutritional Treatment - NAKAJIMA, Mayumi (The Japanese Society of Veterinary Science, 2013)
Rapid turnover proteins, such as transferrin (Tf), are used as dynamic nutritional assessment proteins in human medicine. However, nutritional status in veterinary medicine is mostly assessed on the basis of classical static factors, such as body weight, body condition score and plasma albumin level. This study evaluated the clinical usefulness of Tf as a nutritional assessment marker by measuring plasma Tf concentrations in malnourished dogs before and after nutritional treatment. Posttreatment plasma Tf concentrations were significantly higher than the pretreatment concentrations, although the albumin concentration did not change significantly. The numbers of dogs that exhibited increases in plasma Tf concentrations were significantly related to weight gain. Furthermore, the survival rates at day 60 after treatment initiation were significantly higher in dogs with plasma Tf concentrations above the reference value (180 mg/dl) after the nutritional treatment than in those with a plasma Tf concentration<180 mg/dl. In conclusion, the plasma Tf concentration is related to nutritional condition and would be a candidate for a novel nutritional assessment marker in dogs.